Leveraging customer loyalty in the short term domestic insurance industry through a focus on product stewardship - Staak, Barry John (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2007.